POSITION OF PRIMARY SCHOOLS IN PROVIDING HEALTH EDUCATION AND PROMOTION OF HEALTH LITERACY - Mukaddes Örs; Mesude Uluşen (Informascope, 2015)
This research aims to find out the condition of public primary schools in Manavgat, Antalya in terms of social health care and the learning needs of parents about this issue. The universe of this research that is in screen model comprisespublic primary schools in Manavgat. In data analysis, frequency, percentage and chi square techniqueswere used. The majority of parents who did not take any education about the health education which affect student success are willing to take an education like that. Nearly half of these parents prefer to takethis education at the weekends in the daytime and one third of them prefer this education on weekdays in the daytime. Key words: Health Education, Health Literacy, Student Success, Parent Education